The Potential Usefulness of Peripheral Somatosensory Stimulation in Improving Sleep Quality in Patients with Insomnia - Nussbaum, LA; Janjua, TM; Pederson, J; Nussbaum, ES (Journal of Sleep And Sleep Disorder Research, 2024)
Background Insomnia and other sleep disorders represent a major cause of disability and impaired productivity. We evaluated the impact of peripheral somatosensory stimulation (PSS) on sleep quality in 12 patients with varying degrees of insomnia. Methods Twelve adult patients underwent daily PSS therapy for a 4-week period and were evaluated using the Insomnia Severity Index at baseline (prior to initiation of therapy) and then at the conclusion of the treatments. All data were obtained through a self-reported 7-question survey evaluating overall severity of insomnia symptoms and the impact of sleep patterns on satisfaction with sleep, daily functioning, and overall quality of life. Changes from baseline insomnia scores were analyzed using cumulative link mixed models (CLMMs). Results Seven men and five women completed one month of PSS therapy. Mean age was 55.1 (range 29 to 80 years). No adverse events were described by the patients. The average total change from baseline score was -10.3 points (baseline: 16.5 vs. week 4: 6.2). Patients had statistically significant improvements for every individual survey question by week 4. The median composite score was improved from baseline, with an overall median score of 2 (IQR: 1.25 – 2.75, min-max: 1-4) at baseline compared to 0.5 (IQR: 0 – 0.25, min-max: 0-2) by week 4 (MD = -1 95% CI: , p < 0.001), signaling typically moderate insomnia at baseline vs. typically minimal to no symptoms by week 4. The predicted probability of obtaining the best outcome (score=0) was 9% at baseline vs. 53% by week 4. The overall cumulative odds ratio was 11.9 (p < 0.001), suggesting that on average, the odds of moving from one score to a lower (improved) score at week 4 compared to the baseline are approximately 12 times higher than moving to a neutral or worse score. Conclusions PSS stimulation appeared to have a significantly favorable effect on sleep quality in this group of patients. Symptoms related to ability to fall asleep, remain asleep, and overall quality of sleep were all improved with PSS therapy. We suggest that further investigation into the potential usefulness of PSS therapy in patients with sleep disorders is warranted.
Keywords: anxiety; depression; insomnia; neuromodulation; relaxation; sleep; somatosensory stimulation